ANALISIS PELAYANAN OPERASI DAN PEMELIHARAAN IRIGASI PADA UNIT PELAKSANA TEKNIS SUMBER DAYA AIR DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN MADIUN, PROPINSI JAWA TIMUR TAHUN 2021 - Karon Suprapto; Joko Pramono; Adi Purwanto (JI@P, 2022)
Irrigation Operation and Maintenance cannot be separated from the activities ofproviding services in the field of agriculture through an irrigation network. Thepurpose of the study was to analyze the operation and maintenance of irrigationservices and to examine the efforts of the UPT SDA of the Public Works andSpatial Planning of Madiun Regency in the service of irrigation operations andmaintenance. Validation of data to ensure that between what is observed andresearched is appropriate and really exists and that the event actually happenedand can be trusted. The process of data analysis in this research by studying andreviewing all available data from various sources obtained from directobservation and interviews. The results showed that the irrigation serviceoperation and maintenance process was not optimal, due to the lack ofmaintenance of the irrigation network and the lack of operational andmaintenance personnel for the irrigation network, causing high maintenancecosts, slow irrigation water services to farmers, many damaged sluice gates andwidespread theft of water.Keywords: Maintenance Operations, Irrigation, Tangibles, Qualitative.